Pengaruh Penambahan Sari Ubi Kayu terhadap Mutu Saos Tomat - Krishna Purnawan Candra; Neni Suswatini; Asih Ika Suryandari (agriTECH, 2003)
Starch is the main composition of cassava-extract; therefore it can be used in food product as thickening agent. The purpose of this research was to know the effects of cassava-extract addition in tomato ketchup to its physical properties and consumer's acceptance. Randomized Complete Design was used in this experiment with cassava-extract volume as single factor and arranged in five treatment levels of 0, 20, 40, 60, 80 mL, each with three replications. Tomato paste of 400 mL (300 g) was added by cassava-extract according to the treatment level. The mixture was cooked for 10 minutes following addition of suitable spices. The results of the experiment showed that moisture content of tomato ketchup is around 70-80%, and its volume increase according to the increasing of cassava-extract added. Cassava-extract of 80 mL gave a tomato ketchup yield of 64%. The addition of cassava-extract in tomato ketchup processing gave influence in colour, viscosity, and sweetness of tomato ketchup. and they increased by increasing of cassava-extract addition. According to hedonic quality test, the addition of cassava extract of 60 mL and 80 mL gave a sweet, dark orange, and viscous tomato ketchup. This tomato ketchup was preferred by consumer